2018
DOI: 10.1111/hsc.12695
|View full text |Cite
|
Sign up to set email alerts
|

Exposing the impact of intensive advice services on health: A realist evaluation

Abstract: Attention has turned to welfare advice as a potential health and social care intervention. However, establishing direct evidence of health impact has proven difficult. This is compounded by the need to understand both the facilitative contexts and mechanisms through which this impact occurs. This study investigated if, how and in which circumstances an intensive advice service had an impact on stress and well‐being (as precursors to health impacts), for clients attending a branch of Citizens Advice, located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Mechanism includes two aspects, first the process of reasoning of how subjects interpret and act upon programme intervention, at a given time, in a given context, and secondly how they interact with available programme resources. Outcomes are described as the patterns of intended and unintended consequences that result from mechanisms triggered in different contexts, and may be proximal, intermediate or distal [32,35]. Theories about how programmes are expected to work ("programme theories") are developed based on this configuration and are then iteratively tested and refined with empirical data gathered through appropriate methods and triangulated with available literature [32,36].…”
Section: Methodsmentioning
confidence: 99%
“…Mechanism includes two aspects, first the process of reasoning of how subjects interpret and act upon programme intervention, at a given time, in a given context, and secondly how they interact with available programme resources. Outcomes are described as the patterns of intended and unintended consequences that result from mechanisms triggered in different contexts, and may be proximal, intermediate or distal [32,35]. Theories about how programmes are expected to work ("programme theories") are developed based on this configuration and are then iteratively tested and refined with empirical data gathered through appropriate methods and triangulated with available literature [32,36].…”
Section: Methodsmentioning
confidence: 99%
“…Mechanism includes two aspects, rst the process of reasoning of how subjects interpret and act upon program intervention, at a given time, in a given context, and secondly how they interact with available program resources. Outcomes are described as the patterns of intended and unintended consequences that result from mechanisms triggered in different contexts, and may be proximal, intermediate or distal outcomes [24,28]. Theories about how programs are expected to work ( "program theories") are developed based on this con guration and are then iteratively tested and re ned with empirical data gathered through appropriate methods and against available literature [24,29].…”
Section: Methodsmentioning
confidence: 99%
“…In the period of October 2017 to September 2018, the service as a whole provided 4,141,044 consultations, 55% of which related to state benefits, Universal Credit and debt [31]. Recent research has found that a CA service had a positive impact on its clients through increasing wellbeing and reducing stress [32]. This paper delves further into this experience of stress, and stress relief through the service, concurrently developing further understanding in stress theory and research.…”
Section: Welfare Advice Service Settingmentioning
confidence: 99%
“…This article reports on a secondary data analysis. The original study was a realist evaluation of a CA service in the North East England [32,33]. It is pertinent to look at this geographical location, as it is one of the areas most prominently affected by cuts in the UK [34].…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation